2015
DOI: 10.1038/srep10466
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of kynurenine 3-monooxygenase and effects on proliferation, migration and invasion of human hepatocellular carcinoma

Abstract: Kynurenine 3-monooxygenase (KMO) is a pivotal enzyme in the kynurenine pathway of tryptophan degradation and plays a critical role in Huntington’s and Alzheimer’s diseases. This study aimed to examine the expression of KMO in human hepatocellular carcinoma (HCC) and investigate the relationship between its expression and prognosis of HCC patients. We first analyzed KMO expression in 120 paired HCC samples (HCC tissues vs matched adjacent non-cancerous liver tissues), and 205 clinical HCC specimens using immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 48 publications
3
57
0
Order By: Relevance
“…Also, KMO activity may be involved in tumor immune tolerance. Recent studies have shown that its overexpression is related to rapid cancer progression and a poor prognosis (49,180). Similar to inflammatory-induced IDO1 expression, KMO expression is induced by inflammatory stimuli (181,182).…”
Section: Indoleamine 23-dioxygenase 2 Tryptophan 23-dioxygenase Amentioning
confidence: 97%
“…Also, KMO activity may be involved in tumor immune tolerance. Recent studies have shown that its overexpression is related to rapid cancer progression and a poor prognosis (49,180). Similar to inflammatory-induced IDO1 expression, KMO expression is induced by inflammatory stimuli (181,182).…”
Section: Indoleamine 23-dioxygenase 2 Tryptophan 23-dioxygenase Amentioning
confidence: 97%
“…MZ‐1, a neutralizing monoclonal antibody to POSTN, showed significant growth inhibition both in vivo and in vitro, thereby providing an alternative approach in clinical management of CE patients. KMO is a pivotal enzyme in the kynurenine‐mediated tryptophan degradation pathway; it positively regulates proliferation, migration, and invasion of tumor cells, and may serve as a novel prognostic marker in various cancers . Recently, investigators revealed the crystal structure of Saccharomyces cerevisiae KMO, in the free form and in complex with the tight‐binding inhibitor UPF 648, which will promote the search for new KMO inhibitors in targeted therapies against neurodegenerative diseases and tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Jin et al () detected the expression of KMO in HCC by immunohistochemistry. In vitro studies showed that KMO can absolutely regulate the proliferation, migration, and invasion of HCC cells.…”
Section: The Mechanism Of Kmo In Different Diseasesmentioning
confidence: 99%
“…However, human pancreatitis is highly heterogeneous, so further studies are necessary to demonstrate whether KMO inhibitors are suitable for all pancreatitis (Ray, 2016). Jin et al (2015) detected the expression of KMO in HCC by immunohistochemistry. In vitro studies showed that KMO can absolutely regulate the proliferation, migration, and invasion of HCC cells.…”
Section: Non-neurological Diseasementioning
confidence: 99%